Changes in physical activity and risk of ischemic stroke: The ARIC study - Cowan, Logan T; Tome, Joana; Mallhi, Arshpreet Kaur; Tarasenko, Yelena N; Palta, Priya; Evenson, Kelly R; Lakshminarayan, Kamakshi (International journal of stroke, 2023)
Limited data exist regarding the impact of changes in physical activity (PA) over time on ischemic stroke risk. Exploring this understudied area could help improve stroke prevention strategies and promote PA during the lifespan. We evaluated 11,089 Atherosclerosis Risk in Communities (ARIC) participants recruited in 1987-1989 who completed Visit 3 (1993-1995). We classified PA as meeting recommendations, not meeting recommendations, or no PA. Categories of increased, decreased, stable high, and stable low PA and a continuous PA variable were also evaluated. Crude and adjusted Cox regression models were used to characterize the association of 6-year changes in PA and ischemic stroke risk. Participants had a mean age of 60 years. During a median of 21 years, 762 ischemic stroke events occurred. Compared to the participants with recommended PA at both visits, those with no PA had 46% higher hazards of ischemic stroke (hazard ratio (HR) = 1.46 (95% confidence interval (CI) = 1.17, 1.82)), and those with recommended PA at Visit 1 and no PA at Visit 3 also had 37% higher hazards (HR = 1.37 (95% CI = 1.02, 1.83)). Participants who increased their PA from Visit 1 to Visit 3 had 23% lower hazard than those with stable low PA at both visits (HR = 0.77 (95% CI = 0.63, 0.94)), while those who decreased their PA had 25% higher hazards compared to those with stable high PA at both visits (HR = 1.25 (95% CI = 1.01, 1.54)). Physical inactivity during midlife increases ischemic stroke risk, while meeting PA recommendations reduces it.